Recasting respectability : habitus, call centres and the modern Indian woman : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Sociology, Massey University, Palmerston North, New Zealand - Mishra, Swati (Massey University, 2011)
The unprecedented growth of transnational call centres in metropolitan India has produced a young work force who is subjected to the experiences of a western world, in a global work milieu in both real and virtual ways. The media characterizes this modern career path and life in an urban world as catalysts for westernisation among the call centre employees. The fact that transnational call centres welcome more young women into their fold due to their specific labour requirement, also poses challenges to the gendered norms and values of a patriarchal Indian society, where it is improper for young women to step outside of their family homes during the night. Moreover, women from middle class families form a significant part of this new work force because of the English speaking requirements of the call centre industry. Against such a backdrop, this thesis explores the influences of call centre work and life in the metropolitan city of Bangalore on the emerging gendered subjectivities of young, middle class women. This sociological study has been based on the methods of participant observation and narrative interviews among migrant young women in the age group of 18-25, over a period of 18 months in Bangalore. These women had worked in transnational call centres for a minimum of four years. I explored three ways in which the women identified themselves: in terms of their positioning as daughters in middle class families; in terms of their ambitions to enhance their professional careers and as consumers in a metropolitan city with the financial independence to adopt new consumption practices. The study shows that the aspirations of these young women to acquire a modern persona based on their job in a global industry and to satisfy their sexual desires in the anonymous living conditions prevalent in an urban environment, do not digress completely from the influences of middle class families. It remained embedded within the wider expectations of the middle class families that their daughters should always remain ‘respectable’. The women in my study carried forward this sense of respectability as an integral part of their gendered identities in their work as well as city life. As the women engaged with varying discourses of ‘being respectable’ in a global work place and city, they also reflected on the earlier practices of their families. As creative and reflexive social agents, these women devised new gendered practices which remade some of the familial boundaries of respectability.
Keywords: Call centres; Call centre employees; Working women, India; Bangalore; Respectability; Women in a patriarchal society